Crack initiation processes in acrylic bone cement - Sinnett-Jones, P. E.; Browne, M.; Moffat, A. J.; Jeffers, J. R. T.; Saffari, N.; Buffière, J.-Y.; Sinclair, I. (Journal of Biomedical Materials Research Part B, 2009)
A major constraint in improving the understanding of the micromechanics of the fatigue failure process and, hence, in optimizing bone cement performance is found in the uncertainties associated with monitoring the evolution of the internal defects that are believed to dominate in vivo failure. The present study aimed to synthesize high resolution imaging with complementary damage monitoring/detection techniques. As a result, evidence of the chronology of failure has been obtained. The earliest stages of crack initiation have been captured and it is proposed that, in the presence of a pore, crack initiation may occur away from the pore due to the combined influence of pore morphology and the presence of defects within regions of stress concentration. Furthermore, experimental evidence shows that large agglomerations of BaSO4 are subject to microcracking during fatigue, although in the majority of cases, these are not the primary cause of failure. It is proposed that cracks may then remain contained within the agglomerations because of the clamping effect of the matrix during volumetric shrinkage upon curing. © 2008 Wiley Periodicals, Inc. J Biomed Mater Res, 2009